PENINGKATAN KAPASITAS KELOMPOK SADAR WISATA DESA CAGEUR KECAMATAN DARMA KABUPATEN KUNINGAN MENUJU DESA MANDIRI - Nurdin, Nurdin; Nurlaila, Ai; Kosasih, Dede; Nasihin, Iing; Herlina, Nina (Universitas Ekuitas Indonesia, 2022)
The Cegeur Village Government tasked the Tourism Awareness Group (POKDARWIS) Rangers of Cageur Village, Darma District, and Kuningan Regency with managing the